Developing Fact Finders: A Mobile Game for Overcoming Intractable Conflicts - Nicolaidou, Iolie; Egenfeldt-Nielsen, Simon; Zupančič, Rok; Hajslund, Sara; Milioni, Dimitra L. (My University, 2023)
This study describes the design of a serious game for social change (“Fact Finders”) that presents intergroup conflicts through historical inquiry and multiperspectivity. A pre-test post-test experimental design examined the game’s effect on undergraduates’ perceptions of conflicts in history. Participants included 97 Greek Cypriots (direct parties of the conflict) and 79 Slovenians (third parties of the conflict) who interacted with and evaluated the game online. Data sources included a 17-item questionnaire on perceptions of conflicts in history and gameplay learning analytics data. Findings indicated that both groups’ perceptions for historical source evaluation and understanding multiperspectivity changed significantly after the game. The game significantly changed perceptions about the constructedness of history and the ability to overcome their country’s troubled past only for direct parties of the conflict. The study provides empirical evidence demonstrating the potential value of serious games for affecting young people’s perceptions of intractable intergroup conflicts and their desire to overcome troubled pasts.
Keywords: Serious games for social change; History; Higher education; Intergroup conflicts; Multiple perspectives; Historical source credibility; Historical inquiry